Consumers' Choice Behavior for Cisgenic Food: Exploring the Role of Time Preferences. Issue 2 (10th March 2020) - De Marchi, Elisa; Cavaliere, Alessia; Banterle, Alessandro
Abstract: This paper aims at extending current knowledge on consumer choice behavior on food produced through the application of NBT. We explore whether consumer time preferences and socioeconomic factors may have a role in affecting choice behavior involving cisgenic and conventional products. To this purpose we designed a hypothetical CE and used cisgenic apples as a case study. The results indicate that both time preferences and socioeconomic variables contribute to explain heterogeneity in preference for food products obtained through the application of biotechnologies and provide insight that could be relevant for both the agri‐biotech industry and for policy makers.